An unusual case of an immersion hand presentation in a military signaller operating in the jungle in Belize. Issue 6 (8th August 2017) - Forbes, Kirstie E; Foster, P
Abstract : Belize, hosting one of the British Army's overseas training areas, provides access to challenging terrain and austere environments, which allows the delivery of training to soldiers on survival and combat within the jungle environment. A 26-year-old infanteer on exercise in Belize presented with progressive bilateral dry, painful, oedematous hands, secondary to the harsh environmental conditions of the jungle and inadequate drying of his hands resulting in his inability to perform his combat duties. The symptoms completely resolved with drying, emollient application and analgesia. While there are no reported cases of immersion hand, comparisons can be made with the well-reported warm weather immersion foot. This case highlights the importance of force preparation and soldier education for units deploying to the jungle. Simple preventive measures, including adequate 'wet–dry' drills and use of emollients can reduce the prevalence of immersion hand, a preventable condition, which can have a significant impact on the overall combat effectiveness of the unit.